KAJIAN HUBUNGAN FUNGSIONAL PEMERINTAHAN PUSAT DAN PEMERINTAH DAERAH DALAM PENYELENGGARAAN TATAKELOLA PEMERINTAHAN YANG BAIK - AD. Basniwati; A. Khair; Kafrawi Kafrawi; M. Saleh (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
Based on Article 1 paragraph (6) of the Regional Autonomy Law No. 23 of 2014 the definition of Regional Autonomy is the right, authority, and obligation of an autonomous region to regulate and manage its own Government Affairs and the interests of the local community in the system of the Unitary State of the Republic of Indonesia. In line with this explanation, the regional government system in Indonesia, according to the constitution of the 1945 Constitution of the Republic of Indonesia, is based on the explanation that it is stated that Indonesian regions will be divided into provincial regions and provincial regions will also be divided into smaller regions. In areas that are autonomous or merely administrative in nature, everything is according to the rules that will be determined according to the law. This is a relationship that is based on the context of implementing government programs. Which if interpreted in general is a reciprocal process in the form of a relationship or part that occurs due to process factors, common interests and causal relationships. All of these relationships must be fair and harmonious between the central and local governments.